Contribution of Erythrocytes to Thrombin Generation in Whole Blood - Peyrou, V.; Lormeau, J. C; Hérault, J. P.; Gaich, C.; Pfliegger, A. M.; Herbert, J. M. (Thrombosis and Haemostasis, 1999)
Thrombin generation (TG) initiated by diluted tissue-factor was investigated in whole human blood, in platelet-rich plasma (PRP), in platelet-poor plasma (PPP), and in PPP supplemented with red blood cells (RBCs). TG was characterized by the lag time preceding the thrombin burst and by the endogenous thrombin potential (ETP). RBCs at normal haematocrit were found to influence the lag time to the same extent as platelets. When TG was carried out in PRP or in PPP + RBCs, both the ETP and lag time were dependent on the platelet count or on the haematocrit, but the shapes of the dose-response curves were different. The inhibition of TG in PPP+ RBCs by two direct thrombin and factor Xa inhibitors: hirudin and DX 9065A, and two antithrombin III (AT)-dependent anticoagulants: heparin and SR 90107A was found to be similar to that previously described in PPP and in PRP: hirudin and DX 9065A only delayed TG whereas heparin and SR 90107A both delayed and decreased TG. FACscan analysis following labelling with FITC-annexin V or with phycoerythrin-labelled anti-glycophorin A of samples taken in the course of TG initiated in PPP + RBCs showed that no significant haemolysis occurred and revealed that 0.51 ± 0.075% (mean ± sem, n = 3) of RBCs steadily exposed procoagulant phospholipids on their outer surface throughout the TG course. Furthermore, incubation of factors Xa and Va with washed RBCs sampled during TG in PPP +RBCs resulted in a significant and constant prothrombinase activity.Taken together, these data show for the first time that normal RBCs may participate in the haemostatic process through exposure of procoagulant phospholipids.